The Invasive Species Reynoutria japonica Houtt. as a Promising Natural Agent for Cardiovascular and Digestive System Illness - Liu, Shaoyang; Zhang, Ruiyuan; Zhang, Xing; Zhu, Shun; Liu, Siyu; Yang, Jue; Li, Zhiping; Gao, Tianhui; Liu, Fang; Hu, Huiling (Frontiers in Pharmacology, 2022)
Polygoni Cuspidati Rhizoma et Radix, the dry roots and stems of Reynoutria japonica Houtt. (called Huzhang, HZ in Chinese), is a traditional and popular chinese medicinal herb for thousands of years. As a widely used ethnomedicine in Asia including China, Japan and Korea, HZ can invigorate the blood, cool heat and resolve toxicity, which is commonly used to treatment of favus, jaundice, scald, and constipation. However, HZ is now considered an invasive plant in the United States and many European countries. Therefore, in order to take advantage of HZ and solve the problem of biological invasion, scholars around the world have carried out abundant researches on HZ. Until now, about 110 compounds has been isolated and identified from HZ, in which anthraquinones, stilbenes and flavonoids would be the main bioactive ingredients for its pharmacological properties, such as microcirculation improvement, myocardial protective effect, endocrine regulation, anti-atherosclerotic activity, anti-oxidant activity, anti-tumor activity, anti-viral activity, treatment of skin inflammation, burns and scalds. HZ has a variety of active ingredients and broad pharmacological activities. It is widely used in health products, cosmetics and even animal husbandry feed and has no obvious toxicity. Efforts should be made to develop more products such as effective drugs, health care products, cosmetics, agricultural and animal husbandry products to benefit mankind.